ISO 9001 Quality Approach and Performance Literature Review - Saida, Echour; Taibi, Nbigui (European Scientific Journal, ESJ, 2021)
In the face of changing economic conditions and tougher markets, organizations must increase their competitiveness, increase their flexibility and improve their performance. All now have performance and continuous improvement objectives. Management standards (ISO 9001) are often associated with heavy and procedural systems. On the contrary, they are powerful performance levers for certified organizations. ISO 9000 defines performance as a “measurable result” which is related to the activities, processes, product management (including services) systems or organizations. The purpose of this article is to review the literature on the relationship between quality approach and organization performance, a discussion on the quality practices and performance are presented and conceptual models are proposed.